2013
DOI: 10.1590/1516-3180.20131316t2
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive transcranial magnetic stimulation for improving function after stroke

Abstract: BACKGROUND: It had been assumed that suppressing the undamaged contralesional motor cortex by repetitive low-frequency transcranial magnetic stimulation (rTMS) or increasing the excitability of the damaged hemisphere cortex by high-frequency rTMS will promote function recovery after stroke. OBJECTIVE: To assess the efficacy and safety of rTMS for improving function in people with stroke. METHODS:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
85
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(94 citation statements)
references
References 0 publications
2
85
1
6
Order By: Relevance
“…These individual studies show the promise of cortical stimulation in stroke recovery. Overall, Cochrane Reviews have shown that there are no consistent effects of rTMS (for measurements of daily living, motor function, cognitive function, depression) or tDCS (for aphasia and naming) in comparison with sham-treated patients but suggest that more randomized control trials are required to determine fully the viability of using cortical stimulation in stroke rehabilitation (Hao et al, 2013;Pollock et al, 2014;Elsner et al, 2015). A major issue with cortical stimulation and reproducible outcomes is that many variables must be controlled to include stimulation strength, pattern of stimulation, location of electrodes, and individual variation in recovery (Gomez Palacio Schjetnan et al, 2013).…”
Section: Cortical Stimulationmentioning
confidence: 99%
“…These individual studies show the promise of cortical stimulation in stroke recovery. Overall, Cochrane Reviews have shown that there are no consistent effects of rTMS (for measurements of daily living, motor function, cognitive function, depression) or tDCS (for aphasia and naming) in comparison with sham-treated patients but suggest that more randomized control trials are required to determine fully the viability of using cortical stimulation in stroke rehabilitation (Hao et al, 2013;Pollock et al, 2014;Elsner et al, 2015). A major issue with cortical stimulation and reproducible outcomes is that many variables must be controlled to include stimulation strength, pattern of stimulation, location of electrodes, and individual variation in recovery (Gomez Palacio Schjetnan et al, 2013).…”
Section: Cortical Stimulationmentioning
confidence: 99%
“…However, approximately 20–30% of all stroke survivors do not qualify for CIMT or other rehabilitation strategies. For those patients, mirror therapy,6 motor imagery,7, 8 action observation therapy,9 electrical stimulation (e.g., noninvasive brain stimulation,10, 11, 12 or vagus nerve stimulation13) and robot‐aided sensorimotor stimulation14 have been investigated as possible alternatives over the last several years. Driven by advances in other technological areas such as virtual and augmented reality (VR/AR), robotics, invasive and noninvasive brain‐computer interfaces (BCIs),15 as well as pharmacology,16, 17 post‐stroke motor rehabilitation is now a fast growing, emerging field.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies with healthy participants have highlighted responses following NIBS are variable (Hamada, Murase, Hasan, Balaratnam, & Rothwell, 2013;Hordacre et al, 2017a; Lïżœ opez-Alonso, Cheeran, RĂ­o-RodrĂ­guez, & Fernïżœ andez-del-Olmo, 2014;M€ uller-Dahlhaus, Orekhov, Liu, & Ziemann, 2008). Furthermore, Cochrane reviews have been unable to support use of NIBS as an intervention for stroke survivors as a result of highly variable responses (Elsner, Kugler, Pohl, & Mehrholz, 2016;Hao, Wang, Zeng, & Liu, 2013). Although producing the desired functional benefit in some stroke survivors, NIBS may not be a one-size-fits-all intervention and it may be that some patients experience no functional benefit from cortical stimulation (Hesse et al, 2011;Rossi, Sallustio, Di Legge, Stanzione, & Koch, 2013).…”
Section: Introductionmentioning
confidence: 99%